Disposition, metabolism and mass balance of delafloxacin in healthy human volunteers following intravenous administration. (2nd December 2015) - McEwen, Andrew; Lawrence, Laura; Hoover, Randy; Stevens, Lloyd; Mair, Stuart; Ford, Gill; Williams, Dylan; Wood, Stuart
Abstract: 1. The pharmacokinetics and disposition of delafloxacin was investigated following a single intravenous (300 mg, 100 µCi) dose to healthy male subjects. 2. Mean C max, AUC0–∞, T max and t 1/2 values for delafloxacin were 8.98 µg/mL, 21.31 µg h/mL, 1 h and 2.35 h, respectively, after intravenous dosing. 3. Radioactivity was predominantly excreted via the kidney with 66% of the radioactive dose recovered in the urine. Approximately 29% of the radioactivity was recovered in the faeces, giving an overall mean recovery of 94% administered radioactivity. 4. The predominant circulating components were identified as delafloxacin and a direct glucuronide conjugate of delafloxacin.